GEOCHEMICAL AND Sr, Nd ISOTOPIC SIGNIFICANCE OF POST-COLLISIONAL KEBAN A-TYPE SYENITES, ELAZIG, SOUTHEASTERN TURKEY - Kurum, Sevcan (Carpathian Assoc Environment and Earth Sciences, 2013)
The Cretaceous age plutons with shoshonite affinity occurring in the Keban region (Northwest Elazig in Southeast Anatolia) display A-type magma characteristics (e.g., Nb+Ce+Y+Zr > 400 ppm, Na2O+K2O >8 wt.%). The intrusive bodies comprise syenitic, with rare granodioritic, porphyries. They consist of predominantly K-feldspar and plagioclase, with lesser quartz, amphibole, biotite and pyroxene phenocrysts, and of accessory minerals such as apatite, zircon and zeolite. The plutons are highly enriched in LREE and show significant negative Ba, Nb, Sr and Ti anomalies. Changes in separated K-feldspar crystals (Kiln) (87Sr/86Sr 0.70609-0.70610) and whole rock Sr-Nd (87Sr/86Sr 0.70597-0.70628) isotope composition in terms of some elements and major oxides indicate that fractional crystallisation process took place during the crystallisation of these minerals and rocks. The 143Nd/144Nd ratio measured in one single Kiln sample was 0.51243 which was similar to the 143Nd/144Nd values of 0.51238-0.51242 obtained from the whole rocks. Geochemical and isotopic variations of A-type syenites bearing K-feldspar megacrystals (Kfm) are consistent with those of the lithospheric mantle (EMU) and crustal sources that were modified by subduction zone enrichment. Nd/La (0.4 - 0.8) and Nb/Y (0.45-1.1) ratios imply the role of astenospheric fluids in their origin. The within-plate and late orogenic tectonic settings described in the tectonic discrimination diagrams are conformable with those of A-type magmas. The proposed model supports the fact that the partial melting of both crustal and subduction-modified chemically enriched subcontinental lithospheric sources, which was triggered by an upwelling asthenosphere and underplating, played a significant role in the genesis of Keban A-type syenites. Data also suggests that the A-type Keban syenites are likely formed within the Southeast Anatolian extension-related tectonic system that arosed post- collision of the Eurasia and Arabian plates.
Keywords: A-type syenite; Sr-Nd isotope geochemistry; lithospheric mantle; post-collisional; Keban-Elazig; SE Turkey